Proof of principle for transfusion of in vitro–generated red blood cells - Giarratana, Marie-Catherine; Rouard, Hélène; Dumont, Agnès; Kiger, Laurent; Safeukui, Innocent; Le Pennec, Pierre-Yves; François, Sabine; Trugnan, Germain; Peyrard, Thierry; Marie, Tiffany; Jolly, Séverine; Hebert, Nicolas; et al. (Blood, 2011)
In vitro RBC production from stem cells could represent an alternative to classic transfusion products. Until now the clinical feasibility of this concept has not been demonstrated. We addressed the question of the capacity of cultured RBCs (cRBCs) to survive in humans. By using a culture protocol permitting erythroid differentiation from peripheral CD34+ HSC, we generated a homogeneous population of cRBC functional in terms of their deformability, enzyme content, capacity of their hemoglobin to fix/release oxygen, and expression of blood group antigens. We then demonstrated in the nonobese diabetes/severe combined immunodeficiency mouse that cRBC encountered in vivo the conditions necessary for their complete maturation. These data provided the rationale for injecting into one human a homogeneous sample of 1010 cRBCs generated under good manufacturing practice conditions and labeled with 51Cr. The level of these cells in the circulation 26 days after injection was between 41% and 63%, which compares favorably with the reported half-life of 28 ± 2 days for native RBCs. Their survival in vivo testifies globally to their quality and functionality. These data establish the proof of principle for transfusion of in vitro–generated RBCs and path the way toward new developments in transfusion medicine. This study is registered at http://www.clinicaltrials.gov as NCT0929266.